Knowledge, Attitudes and Behavior of Nursing Students Towards the Covid-19 Pandemic In Indonesia - Aminah Aminah; Eli Amaliyah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Coronavirus disease 2019 (COVID-19) is an emerging respiratory disease caused by the new coronavirus and was first detected in December 2019 in Wuhan, China. As a prospective nurse professional who will engage with patients or partners for counseling about pregnancy decision-making and provide health education. During this pandemic period, there was no research that identified the knowledge, attitudes and behavior of students towards the 2019 coronavirus in Indonesia. The purpose of this study is to find out the description of the knowledge, attitudes, and behavior of nursing students against COVID-19 in Indonesia. This cross-sectional survey was conducted from May June 2020. The data was collected online by relying on the writer's network with nursing lecturers in Indonesia and posting to several groups on social media. The inclusion criteria were (i) being a nursing student with Indonesian nationality; (ii) acknowledges the consent given prior to the completion of the survey. A developed questionnaire of knowledge, attitudes and practices towards COVID-19 was used. The majority of participants included in the study (more than 80%) had a high level of caution regarding droplets and air isolation during the COVID-19 outbreak which indicates that most participants had a positive attitude towards COVID-19. More than 80% of participants agreed that COVID-19 will finally be brought under control and belief that Indonesia can win the battle against the COVID-19. This study can be used as a reference in developing policies for nursing institutions during the 2019 coronavirus pandemic in Indonesia. Abstrak: Coronavirus 2019 (COVID-19) adalah penyakit pernapasan yang muncul akibat virus corona baru dan pertama kali terdeteksi pada Desember 2019 di Wuhan, China. Sebagai calon perawat profesional yang akan terlibat dengan pasien atau mitra untuk konseling tentang pengambilan keputusan kehamilan dan memberikan pendidikan kesehatan. Selama periode pandemi ini, belum ada penelitian yang mengidentifikasi pengetahuan, sikap dan perilaku mahasiswa terhadap virus corona 2019 di Indonesia. Tujuan penelitian ini adalah untuk mengetahui gambaran pengetahuan, sikap, dan perilaku mahasiswa keperawatan terhadap COVID-19 di Indonesia. Survei cross-sectional ini dilakukan pada Mei-Juni 2020. Pengumpulan data dilakukan secara online dengan mengandalkan jejaring penulis dengan dosen keperawatan di Indonesia dan diposkan ke beberapa kelompok di media sosial. Kriteria inklusi adalah (i) menjadi mahasiswi keperawatan berkebangsaan Indonesia; (ii) mengakui persetujuan yang diberikan sebelum survei selesai. Kuesioner pengetahuan, sikap dan praktik yang dikembangkan terhadap COVID-19 digunakan. Mayoritas peserta yang termasuk dalam penelitian (lebih dari 80%) memiliki tingkat kewaspadaan yang tinggi terkait tetesan dan isolasi udara selama wabah COVID-19 yang menunjukkan bahwa sebagian besar peserta memiliki sikap positif terhadap COVID-19. Lebih dari 80% peserta setuju bahwa COVID-19 pada akhirnya akan dikendalikan dan diyakini bahwa Indonesia dapat memenangkan pertempuran melawan COVID-19. Kajian ini dapat dijadikan acuan dalam menyusun kebijakan institusi keperawatan pada saat pandemi virus corona 2019 di Indonesia.